A Sandwich-Structured Hybrid Anode With Nitrogen-Doped Amorphous Carbon Nanoarrays Vertically Anchoring on Graphene Nanoplatelets for High Rate Li Storage - Zou, Zhimin; Wu, Limin; Chen, Jianwei; Jiang, Chunhai (Frontiers in Materials, 2018)
Graphene is not an ideal anode material of Li-ion batteries because of its low packing density and low initial Coulombic Efficiency although it shows much higher specific capacity than graphite. Herein, we report a sandwich-structured hybrid anode material which integrates the nitrogen-doped amorphous carbon nanoarrays on both sides of graphene nanoplatelets. The former provides high capacity and excellent rate capability, while the latter stabilizes the cycle performance, both of them brought out outstanding electrochemical properties to the hybrid anode. High discharge capacities of 562 and 217 mA h g-1 are obtained at current densities of 0.1 and 3 A g-1, respectively, which are much higher than those of the starting graphene nanoplatelets (404 and 81 mA h g-1, respectively). Moreover, a discharge capacity of 540 mA h g-1 is maintained after 300 cycles at 0.5 A g-1, demonstrating an excellent cycle stability. This study provides a facile process to prop up the 2 D graphene nanoplatelets with vertically aligned carbon nanoarrays, which may push forward the application of graphene as anode material of Li-ion batteries because of the avoided aggregation and additional Li storage capacity contributed by the N-doped amorphous carbon.